The red badge of courage ebook An episode of the american civil war. - Crane, Stephen (Duke Classics, 2012)
Hailed as one of American literature's most influential works, The Red Badge of Courage has a young recruit facing the trials and cruelties of war. Stephen Crane's 1895 novel is set in the American Civil War. Private Henry Fleming flees from battle and his battalion, considering all lost. Stumbling upon injured soldiers, he feels the shame of deserting and of not possessing the "red badge of courage", the wounds of war. But later when Henry rejoins his regiment and is ordered into a hopeless battle, he finds a chance to finally prove his courage as a man.